A Review of Mycotoxins Produced by Fruit Spoilage Fungi: Mycotoxins from Fruit Spoilage Fungi - Iqbal, Muhammad Naeem; Iqbal, Iqra; Yunus, Fakhar-un-Nisa; Muhammad, Ali; Shahzad, Mirza Imran (PSM Biological Research, 2021)
Fungi invade commodities extensively consumed by humans and animals and produce as secondary metabolites, low molecular weight compounds known as mycotoxins. The proliferation of various fungi in fruits leads to reduction in yield and quality with significant economic losses. Although the most important mycotoxins produced by the fruit spoilage fungi are aflatoxins, ochratoxin A, patulin, and the Alternaria toxins alternariol, alternariol methyl ether, and altenuene, the type, and level of mycotoxins vary by fruit type and geographic location. The increased concern about fruit safety has led to increased studies throughout the world and enhanced awareness for strict regulations governing mycotoxin limits in food. This review aims to explore the mycotoxins produced by fruit spoilage fungi and different factors that affect mycotoxin production and their control methods.